2015
DOI: 10.1523/jneurosci.5272-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Pten Mutations Alter Brain Growth Trajectory and Allocation of Cell Types through Elevated  -Catenin Signaling

Abstract: Abnormal patterns of head and brain growth are a replicated finding in a subset of individuals with autism spectrum disorder (ASD). It is not known whether risk factors associated with ASD and abnormal brain growth (both overgrowth and undergrowth) converge on common biological pathways and cellular mechanisms in the developing brain. Heterozygous mutations in PTEN (PTEN ϩ/Ϫ ), which encodes a negative regulator of the PI3K-Akt-mTOR pathway, are a risk factor for ASD and macrocephaly. Here we use the developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 71 publications
13
91
0
Order By: Relevance
“…We used a Cre driver that is expressed broadly in the cortex, rather than a Cre driver that is restricted to subcortical-projecting pyramidal cells, because we do not know at present if the effects of Pten +/− mutations on the development of this neuronal population are cell autonomous or non-cell autonomous. We have previously shown that Emx1-Cre + ; Pten loxp/+ mice recapitulate the cortical overgrowth phenotype seen in germ-line Pten +/− mice19. Testing social behaviour using three-chamber social approach test, we found that although adult female Emx1-Cre + ; Pten loxp/+ mice did not display a significant difference in allocation of chamber time as compared with controls, a within-group analysis revealed a lack of significant difference in time spent in the stimulus mouse versus object chambers (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We used a Cre driver that is expressed broadly in the cortex, rather than a Cre driver that is restricted to subcortical-projecting pyramidal cells, because we do not know at present if the effects of Pten +/− mutations on the development of this neuronal population are cell autonomous or non-cell autonomous. We have previously shown that Emx1-Cre + ; Pten loxp/+ mice recapitulate the cortical overgrowth phenotype seen in germ-line Pten +/− mice19. Testing social behaviour using three-chamber social approach test, we found that although adult female Emx1-Cre + ; Pten loxp/+ mice did not display a significant difference in allocation of chamber time as compared with controls, a within-group analysis revealed a lack of significant difference in time spent in the stimulus mouse versus object chambers (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, we have found that conditional homozygous mutation of Pten leads to massively increased p-S6 levels and decreased cell density throughout the newborn cerebral cortex, consistent with widespread hypertrophy, whereas we did not observe this phenotype upon conditional heterozygous mutation of Pten (ref. 19). We attribute this to an effect of Pten dosage: homozygous mutation of Pten shifts a wide variety of neural cell types towards a pathological state, with strong upregulation of mTORC1 activity and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PTEN has recently been identified to function with β-catenin to regulate normal brain growth, implicating PTEN in Wnt signaling. It was discovered that β-catenin signaling is elevated in a mouse model of Pten ( Pten +/-), and a heterozygous mutation in β-catenin suppresses the excessive cortical brain growth in Pten +/- mice [53]. This indicates that multiple ASD risk factors likely converge upon neural progenitor proliferation during embryonic brain development, potentially through regulation of canonical Wnt signaling.…”
Section: Reviewmentioning
confidence: 99%
“…However, there is also evidence that DISC1 is required for development of glutamatergic synapses [275,276], although it is not yet clear if this function is Wnt-dependent. The gene encoding PTEN, a cytoplasmic protein that suppresses Wnt/β-catenin signaling in the developing mouse cortex [277], has been repeatedly identified as a high-risk ASD susceptibility gene in human genomic studies [278,279,280,281]. Finally, single nucleotide variants of the Wnt/PCP pathway genes PRICKLE1 and PRICKLE2 were identified in whole exome sequencing of affected families [237,282].…”
Section: Human Genomic Studiesmentioning
confidence: 99%